3D S-wave velocity modelling with surface waves in oil seismic prospecting. Issue 2 (4th March 2021) - Wang, Zhinong; Sun, Chengyu; Wu, Dunshi; Wang, Yumei
Abstract : It is a convenient and effective way to infer near-surface S-wave velocity ( V S ) structures by using seismic surface waves. In spite of many successful applications on the geotechnical or engineering scale, surface-wave analysis and inversion methods are still not widely used in oil seismic exploration. Particularly, there are few researches reported on the three-dimensional (3D) V S structure modelling with the surface wave methods on this exploration scale. In this paper, we proposed a seismic surface wave data processing and inversion scheme for 3D near-surface V S modelling, and applied it to a field seismic data acquired for oil prospecting in Eastern China. Firstly, we analysed and adjusted the acquisition geometry to suit surface-wave analysis. Next, the interpolation and stacking processing was applied to the seismic data to eliminate spatial aliasing and improve the quality of dispersion images. In term of phase velocity dispersion imaging method, we adopted the cross-correlation and phase-shifting (CCPS) method to acquire accurate dispersion images. Simultaneous linearisation inversion of V S and layer thickness was used to inverse the surface wave dispersion curves. This inversion method reduces dependence of the initial models and has ability to detect the top interface of high-velocity layer. At last, the 3D near-surface V S structure was constructed by interpolating the all of 360 1D V S structures. We contrasted the surface wave inversion result with the first-arrival tomography inversion result, and the geological stratification results of both were coincident. Within the near-surface range, the surface wave inversion result has a higher resolution. This confirms that 3D V S modelling with surface waves in oil seismic prospecting is effective and practical.